INNOVATIVE MANAGEMENT FRAMEWORKS FOR SUSTAINABLE RURAL ENTERPRISES BASED ON DIGITAL TRANSFORMATION AND INSTITUTIONAL RESILIENCE TO ACHIEVE SUSTAINABLE LONG-TERM CHANGE - Leroy Samy Uguy; Esther Kembauw; Maulida Nurfajrianty (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
Our study explores how Village Owned Enterprises (Badan Usaha Milik Desa, or BUM Desa) have become the paradigm for modern management that aims to reveal business sustainability. In making that transformation from mere ‘nameplates’ onto a strong position in the global market, these rural institutions utilize new means of reach through digital-savvy marketing with teaming up and assets-based growth management. Based on the evidence collected by TEKAD and from relevant case studies, we developed a management framework that balances economic and social objectives with environmental stewardship. As it turns out, the way forward for sustainable business is technological leapfrogging, inclusive governance and social versus commercial hybrid.